CSP plants with thermocline thermal energy storage and integrated steam generator – Techno-economic modeling and design optimization. (15th November 2017) - Pizzolato, A.; Donato, F.; Verda, V.; Santarelli, M.; Sciacovelli, A.
Abstract: Although CSP has reached technological maturity, high capital investment and specific electricity cost remain the major development barriers. To reduce them, highly efficient, integrated, and cheaper CSP components are urgently needed. In this paper, we investigate a novel CSP plant configuration with a single-tank Thermal Energy Storage (TES) fully integrated with the steam generator. The objective of this research is twofold: i) provide a reliable model of single-tank thermal storages with integrated steam generator; ii) identify two optimized CSP plant designs to achieve best energetic and economic performances. To achieve these aims we developed a numerical model of the main system components and validated it against experimental data. This model was then integrated in a full simulation and heuristic design optimization of the plant. The results revealed that the system proposed can generate electricity in middle-Italy (Rome) at a cost of 230.25 $/MWh with a 15% reduction compared to the double tank option. Furthermore, if cogeneration is used to recover the waste heat, this system is an interesting option for users such as small districts, university campuses and hospitals. In the latter case, the optimized system pays off in 6 years and covers 80% of the heating and cooling requirements. Highlights: A novel CSP plant with thermocline TES and integrated steam generator is modeled in details. The solar field and the integrated TES models are validated with experimental data. The single tank configuration lowers the LEC of 42 $/MWh. Cogeneration lowers the LEC of 28%.